The reptile room - Snicket, Lemony (A series of unfortunate events ;, 1999)
After narrowly escaping the menacing clutches of the dastardly Count Olaf, the three Baudelaire orphans are taken in by a kindly herpetologist with whom they live happily for an all-too-brief time.